Implementing dynamic evolution control approach for DC-link voltage regulation of superconducting magnetic energy storage system. (February 2018) - Penthia, Trilochan; Panda, Anup Kumar; Sarangi, Sunil Kumar
Highlights: A dynamic evolution control scheme is proposed to regulate the DC-link voltage. Governing switching state function(s) is formulated for each converter. The harmonic contents of the SMES magnet current are significantly reduced. Source current is upheld balanced and less distorted regardless of load profile. AC loss reduction and homogeneous voltage distribution are achieved. Abstract: A Dynamic Evolution Control (DEC) scheme for the Superconducting Magnetic Energy Storage (SMES) system is presented in this article. The DC-link voltage of Power Converter Unit (PCU) is strictly regulated by the proposed control scheme irrespective of load transients. In SMES system, the PCU interfaces the SMES magnet and the AC system in order to give an efficient power exchange, and high quality power flow in the grid. Especially, this paper focuses on power quality improvement, and homogeneous voltage distribution & AC loss reduction across the magnet by achieving excellent DC-link voltage regulation. The harmonic components of magnet current are analyzed which are responsible for AC losses. It has been observed that the 3rd, 4th, 5th, 6th and 7th order harmonic components of the magnet current are significantly reduced. Particularly, a homogeneous voltage profile and less distorted magnet current are attained using the control scheme. The system supply current is found almost balanced, and its Total Harmonic Distortion (THD) is found well below 5 % . Moreover, the control performance of DEC scheme is compared with that of the Proportional-Integral (PI) control technique. The proposed system is validated both in MATLAB/SIMULINK and real-time environment using a digital signal processor (dSPACE1104).